Segmenting Consumers in Food and Grocery Retail - Sreelata; Narasimham, N. V.; Gupta, M. K. (Indian Journal of Marketing, 2016)
This study was conducted for identification of the factors in consumer behaviour in retail buying, to identify the elements of pricing that influenced consumers, and to identify important non-pricing factors with respect to buying of groceries and consumer goods like staples (atta, rice, cooking oil, sugar, and so forth), personal care and toiletries (oil, shampoo, soaps), and fruits&vegetables. These items constitute a major part of the monthly grocery requirements of consumers, which is a part of food&grocery retail. The paper tried to ascertain the dimensions on which consumers can be segmented on the pricing factors. A survey of 450 households in Delhi&Faridabad found three clusters which have different characteristics. The study makes suggestions to retailers on the basis of the findings of the study.